Sintering of NiO/YSZ Anode Layers for Metal-Supported Solid Oxide Fuel Cell; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Soloviev A. A. Andrey Aleksandrovich; Ionov I. V. Igor Vyacheslavovich; Kovalchuk A. N. Anastasia Nikolaevna; Kirdyashkin A. I. Aleksandr Ivanovich; Maznoy A. S. Anatoly Sergeevich; Kitler V. D. (Advanced Materials and Nanotechnology, 2014)
Title screen